Research status in Traditional Chinese Medicine nursing of epigastric pain (胃脘痛的中医护理研究现状) - GAO Qianqian (高倩倩) (Association of Integrative Nursing, 2023)
Epigastric pain is a common gastric disease. Traditional Chinese Medicine nursing technology has been proven to be effective in the nursing of spleen and stomach diseases, with the advantages of rapid response, simple operation, wide application range, low cost and easy acceptance to patients. This article analyzes the current situation of Traditional Chinese Medicine nursing application in management of epigastric pain and analyzes the future research progress. (胃脘痛是常见的胃部疾病。中医护理技术在脾胃疾病护理中的应用效果良好, 具有见效快、操作简单、适用范围广、成本低廉、患者易接受等优势。本研究就胃脘痛的中医护理应用现状进行综述, 总结现状, 分析发展方向, 旨在为进一步规范胃脘痛中医护理方案提供参考。)